A very rare complication of frontal sinusitis: Pott’s puffy tumor - Parlak, Furkan; Bahceci, Busra; Cam, Betul; Uzun, Ozlem; Coskun, Abuzer (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
Introduction. Pott’s puffy tumor is a very rare clinical condition characterized by subperiosteal abscess, a complication of frontal sinusitis, or as a result of head trauma. Aim. Early diagnosis of this condition is significantly important to prevent sequelae and severe neurological complications. This phenomenon, which is generally seen in children, can rarely be encountered in adults. Description of the case. In this report, we share a rare case of Pott’s puffy tumor in an adult patient. Conclusion. Pott’s puffy tumor, a rare complication of frontal sinusitis, should be considered to prevent neurological and intracranial complications.
Keywords: emergency; headache; Pott’s puffy tumor